Biomarkers of Inflammation in Obesity-Psoriatic Patients - Carmen Rodríguez-Cerdeira; Mónica Cordeiro-Rodríguez; Miguel Carnero-Gregorio; Adriana López-Barcenas; Erick Martínez-Herrera; Gabriella Fabbrocini; Ardiana Sinani; Roberto Arenas-Guzmán; José Luís González-Cespón (Hindawi Limited, 2019)
Psoriasis is a common chronic inflammatory multisystemic disease with a complex pathogenesis consisting of genetic, immunological, and environmental components. It is associated with a number of comorbidities, including diabetes, metabolic syndrome, obesity, and myocardial infarction. In addition, the severity of psoriasis seems to be related to the severity of obesity. Patients with higher levels of obesity show poorer response to systemic treatments of psoriasis. Several studies have demonstrated that white adipose tissue is a crucial site of the formation of proinflammatory adipokines such as leptin, adiponectin, and resistin and classical cytokines such as interleukin- (IL-) 6 and tumour necrosis factor-α. In psoriasis, due to the proliferation of Th1, Th17, and Th22 cells, IL-22, among others, is produced in addition to the abovementioned cytokines. With respect to leptin and resistin, both of these adipokines are present in high levels in obese persons with psoriasis. Further, the plasma levels of leptin and resistin are related to the severity of psoriasis. These results strongly suggest that obesity, through proinflammatory pathways, is a predisposing factor to the development of psoriasis and that obesity aggravates existing psoriasis. Different inflammatory biomarkers link psoriasis and obesity. In this paper, the most important ones are described.